PEMAHAMAN KEBERAGAMAAN DAN SIKAP TUAN HAJI TERHADAP AKTIVITAS PERTAMBANGAN TIMAH DI PULAU BANGKA (Studi Kasus di Desa Lubuk Besar, Kec. Lubuk Besar, Kab. Bangka Tengah, Bangka Belitung) - , Ahmad Syarif H; , Dr. Zainal Abidin Bagir, MA., ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Unconventional tin mining activities are one factor that effect environmental crisis in Bangka island, especially in Desa Lubuk Besar, Kecamatan Lubuk Besar, Kabupaten Bangka Tengah. These activities done by Desa Lubuk Besar people, not only by common people but also by religious leaders like Tuan Haji. These mining activities especially done by Tuan Haji are very interesting to be discussed especially on their religiosity understandings of the relation between human and nature. Tuan Haji was chosen here as research subject is because of their significant rules in the societies and then their religiosity understandings on and their attitudes toward nature are the main focuses of this research. This research was field research with anthropological approach. The process of collecting data was done through interview and observation techniques. To analyze the religiosity understandings of Tuan Haji on the relation between human and nature, used text analyze methods with ecological ethic approaches. By those methods, it could be found that the Tuan Hajiâs understandings were classified into two categories of understanding, anthropocentrism and biocentrism understandings. To analyze the attitude of Tuan Haji toward tin mining activities which is main factor of environmental crisis in Desa Lubuk Besar, used attitude theory that issued by David O. Sears. According to Sears, human attitude toward something around him was formed of three main components